Chess In Schools - Wilbert A. Kieboom (Մանկավարժ հրատ․)
Chess is an educational tool with many possibilities for education. The game contributes to the cognitive, social, emotional and metacognitive development of children according to Karel van Delft, Youth chess trainer, Psychologist and Journalist. (www.chesstalent.com) This is partly due to intrinsic features of the game and partly due to chess teaching methods. The questions that are raised are, why are chess lessons taught in schools? What is the relationship between intelligence and chess? What is a good teaching method? Is chess useful because of its cognitive transference effects on other areas of learning or is it a great tool for developing social and emotional skills? Chess is a metaphor for life. You analyse, make plans, make decisions and look for creative solutions (cognitive). You learn self management, collect, deal with challenges (emotionally). You discuss situations with others (socially). You learn to think through your behavior and situations. (metacognitive). There is a distinction between playing games and solving propositions (diagrams). With games you have to think divergently. You have to come up with ideas yourself to achieve a good result. Like with mini games. With diagrams you have to think convergently, find the right solution. A distinction can be made between the various aspects of the game of chess, for example principles, tactics, strategy and for example the cognitive age of students, gender of students, transfer domains or areas where chess could possibly exert positive learning effects. What I have noticed is that some effects require an incubation period and only occur after a minimal number of chess lessons. My experience is that the turnover point comes after 6 to 7 lessons. I also have been able to personally observe the Hawthorne effect, where students in a chess class receive more personal attention and that motivates them in turn to learn and perform better in many fields and areas of life. I am a strong advocate to not only look at the traditional skills as learned in school , but also focus on the soft skills that help them further progress in their life.
Keywords: Chess